The Illusion of Moral Superiority - Tappin, Ben M. (Soc Psychol Personal Sci, 2016)
Most people strongly believe they are just, virtuous, and moral; yet regard the average person as distinctly less so. This invites accusations of irrationality in moral judgment and perception—but direct evidence of irrationality is absent. Here, we quantify this irrationality and compare it against the irrationality in other domains of positive self-evaluation. Participants (N = 270) judged themselves and the average person on traits reflecting the core dimensions of social perception: morality, agency, and sociability. Adapting new methods, we reveal that virtually all individuals irrationally inflated their moral qualities, and the absolute and relative magnitude of this irrationality was greater than that in the other domains of positive self-evaluation. Inconsistent with prevailing theories of overly positive self-belief, irrational moral superiority was not associated with self-esteem. Taken together, these findings suggest that moral superiority is a uniquely strong and prevalent form of “positive illusion,” but the underlying function remains unknown.